Review of Indonesian Education (Analysis of Secularization of Teaching Materials) - Amir Reza Kusuma; Khoiruddin Abdullah (LECTURES: Journal of Islamic and Education Studies, 2025)
Currently, Muslims are facing various invasions of foreign thoughts that can damage the minds of the people, such as the entry of foreign thoughts from the West, including secularism. This paper seeks to discuss the secularization of education in Indonesia. One of the processes of entering Western thought in the realm of education is through secularization. Secularization has taken place on several teaching materials in schools in Indonesia. Like a history lesson that teaches that human ancestors were from the monkey nation which has evolved millions of years ago, so that religious values ​​that can actually shape morals or in Islam are known as morals, will not be achieved. In fact, many students who are still in school are trapped in free sex, promiscuity and drugs. Of course, this is very dangerous for the younger generation of this nation. When compared, the Western view with the Islamic view of life has far differences. Islam is based on revelation, hadith, reason, experience and intuition, and has a non-dichotomous or tawhidi approach. While the West does not have it, it cannot be equated, so this paper seeks to discuss the secularization of education in Indonesia